Genomic characterization of multi-drug resistant Enterococcus faecalis strain CE_3_5 - Elif Bozcal; Sila Tekiner; Deniz Nazli Guler; Elif Goksu Asal (Journal of Global Antimicrobial Resistance)
AIM: It was aimed to reveal antibiotic resistance genes and virulence factors acquired by the foodborne Enterococcus faecalis CE_3_5 strain via whole genome sequencing analysis. BACKGROUND: Enterococcus species are members of a commensal microflora in the gastrointestinal system of humans and animals. Although they are quite common in milk and dairy products such as cheese, they have recently emerged as hospital-and community-acquired pathogens. Since food is proposed as a significant vector for transmitting antibiotic-resistant enterococcal isolates, E. faecalis strains might have acquired or intrinsic antibiotic resistance genes and virulence determinants. METHODS: The whole genome sequencing of multi-drug resistant E. faecalis strain CE_3_5 isolated from white cheese was performed via Illumina NovaSeq 6000 Platform. Intrinsic and acquired antibiotic resistance genes, chromosomal virulence factors, Sequence Type (ST), and mobile genetic elements have been investigated. RESULTS: The ST of E. faecalis strain CE_3_5 was ST 55. It has been revealed that the E. faecalis strain CE_3_5 was resistant to fluoroquinolones, chloramphenicol, erythromycin, and tetracycline antibiotics. Some of the virulence determinants identified include enterococcal leucine-rich protein A, pilus protein, adhesins, hyaluronidase, thiol peroxidase, and phage-associated proteins. The plasmid replicons were designated as rep7a, repUS43, repUS12, and rep2. Mobile genetic elements associated with resistance were conjugative transposon (Tn6009), and insertion sequences (ISEnfa1, IS1062, IS5). CONCLUSIONS: Foods of animal origin, such as cheese, can constitute reservoirs or contamination of enterococci with antibiotic-resistant properties and virulence factors, providing useful data for risk assessment and indicating that these foods may pose a public health risk to consumers.